Wideband Flexible/Transparent Connected-Ground MIMO Antennas for Sub-6 GHz 5G and WLAN Applications - Arpan Desai (IEEE, 2021)
A flexible transparent wideband four-element MIMO antenna with a connected ground plane is proposed with numerical computation and experimental measurement studies. The optical transparency is obtained using flexible conductive oxide material AgHT-4 and Melinex substrate. The radiating elements are in the form of circular stub-loaded C-shaped resonators, which are positioned in a carefully structured flexible Melinex substrate with an interconnected partial ground plane structured in the form of an L-shaped resonator, attaining an overall antenna size of $0.33λ × 0.48λ $ at the lowest operating frequency. The proposed antenna spans over a −10 dB impedance bandwidth of 2.21–6 GHz (92.32%) with an isolation level greater than 15dB among all elements. The maximum gain is 0.53dBi with a minimum efficiency of 41%, respectively which is satisfactory considering flexible structure and sheet impedance of $4Ω $ /sq. MIMO antenna parameters in terms of the envelope correlation coefficient (ECC) and diversity gain (DG) are also extracted where all the values are satisfactory for MIMO applications. The bending analysis of the proposed transparent MIMO antenna along the X and Y axis has revealed good performance in terms of scattering parameters and radiation pattern along with MIMO diversity performance. All of these technical points make the flexible MIMO antenna suitable for smart devices using sub-6 GHz 5G and WLAN band in IoT applications where visual clutter and co-site location issues need to be mitigated with the integration ease of conformal placement on the curved component/device surfaces.